Apical extrusion of debris by manual and mechanical instrumentation - Leonardi,Lilia E. (2007)
The aim of the present study was to assess the presence of apically extruded debris and evaluate the influence of canal curvature on the amount of debris produced by manual and mechanical techniques. Forty single-rooted mature teeth with 15 to 30 degree of root canal curvature were selected. The presence of only one foramen was confirmed using a magnifying lens. A size 15 K-file was placed up to the apical foramen to determine the patency. Working length was determined with the same instrument, 1 mm short of the foramen. According to the employed technique, the groups were labeled as follows: Group 1 - Manual instrumentation with Mor-flex files; Group 2 - Mechanical instrumentation with Cursor and Mor-flex files; Group 3 - Manual instrumentation with Flexi-cut files; Group 4 - Mechanical instrumentation with Cursor and Flexi-cut files. During instrumentation, the root canals were irrigated with 20 mL. Debris extruded through the apical foramen was collected using the Myers and Montgomery technique. The values (in mg) were: Group 1: 0.422 ± 0.683; Group 2: 0.688 ± 0.795; Group 3: 0.409 ± 0.323; Group 4: 0.810 ± 0.708. Data were analyzed statistically by ANOVA at 5% significance level. There was no statistically significant difference among the groups (p<0.05). No statistically significant differences were found between slight and moderate curvatures in terms of the amount of extruded debris (p>0.05).